Monoclonal antibodies: A review of therapeutic applications and future prospects - Mahmuda A.; Bande F.; Al-Zihiry K.J.K.; Abdulhaleem N.; Majid R.A.; Hamat R.A.; Abdullah W.O.; Unyah Z. (Pharmacotherapy Group, 2024)
Indexed by WOS/ Scopus